Characterisation of mesothelioma-initiating cells and their susceptibility to anti-cancer agents - Pasdar, Elham Alizadeh; Smits, Michael; Stapelberg, Michael; Bajzikova, Martina; Stantic, Marina; Goodwin, Jacob; Yan, Bing; Štursa, Jan; Kovarova, Jaromira; Sachaphibulkij, Karishma; Bezawork-Geleta, Ayenachew; Sobol, Margaryta; et al. (PLoS One, 2015)
Malignant mesothelioma (MM) is an aggressive type of tumour causing high mortality. One reason for this paradigm may be the existence of a subpopulation of tumour-initiating cells (TICs) that endow MM with drug resistance and recurrence. The objective of this study was to identify and characterise a TIC subpopulation in MM cells, using spheroid cultures, mesospheres, as a model of MM TICs. Mesospheres, typified by the stemness markers CD24, ABCG2 and OCT4, initiated tumours in immunodeficient mice more efficiently than adherent cells. CD24 knock-down cells lost the sphere-forming capacity and featured lower tumorigenicity. Upon serial transplantation, mesospheres were gradually more efficiently tumrigenic with increased level of stem cell markers. We also show that mesospheres feature mitochondrial and metabolic properties similar to those of normal and cancer stem cells. Finally, we show that mesothelioma-initiating cells are highly susceptible to mitochondrially targeted vitamin E succinate. This study documents that mesospheres can be used as a plausible model of mesothelioma-initiating cells and that they can be utilised in the search for efficient agents against MM.
Keywords: transplantace nádorů; nádorové biomarkery; invazivní růst nádoru; Biomarkers, Tumor; CD24 Antigen; Neoplasm Invasiveness; Cell Adhesion; Cell Proliferation; Humans; Mitochondria; nádorové buněčné linie; Antineoplastic Agents; Lung Neoplasms; zvířata; Neoplasm Transplantation; Spheroids, Cellular; tokoferoly; Phenotype; protinádorové látky; antigen CD24; myši nahé; Gene Knockdown Techniques; nádory plic; mitochondrie; proliferace buněk; Disease Progression; inhibiční koncentrace 50; fenotyp; Mice, Nude; Inhibitory Concentration 50; Animals; nádorové kmenové buňky; buněčná adheze; lidé; Cell Line, Tumor; mezoteliom; Neoplastic Stem Cells; Mesothelioma; Tocopherols; progrese nemoci; genový knockdown; buněčné sféroidy